PENGARUH SOSIAL EKONOMI DAN KEMANDIRIAN TERHADAB PRESTASI BELAJAR SISWA SMPN 1 PAMUKAN UTARA - Faisal Batennie (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
The purpose of this study is (1) to determine the effect of family socioeconomic status on mathematics learning achievement of students of class VIII in SMP Negeri I Pamukan Utara. (2) to determine the effect of student independence on mathematics learning achievement of students of class VIII in SMP Negeri I Pamukan Utara. The method used in this study is a regression research method with a quantitative approach that is research that examines to see the effect of using numbers ranging from data collection, interpretation of the data, as well as the appearance of the results. In addition to data in the form of numbers, in quantitative research there is also data in the form of qualitative information. While this type of research is a simple regression research that is research that aims to see the effect between two or more variables. If there is an influence, how close is the influence and meaning or not that influence. Keywords: Family Socio-Economic Status, Student Independence, Achievement.